"Stil" v rečevom soznanii russkih školʹnikov - Gol’din, Valentin E. (Stylistyka, 2021)
The article explains the scope of the term stil ’ (style) in the Russian explanatory dictionaries as compared to the corresponding article in the schoolchildren association dictionary. The latter is organized as a frame suggesting the associative fields of the word. The author claims that the core meaning of the word stil’ in the language consciousness of modem Russian schoolchildren mainly relates to the domain of fashion, and not to the communicative field of art, as it appears from the explanatory dictionaries. The stated distinction may be explained by severa! reasons: the explanatory dictionaries summarize the examples from written texts, whereas the schoolchildren association dictionary is more closely connected to the orał speech; the explanatory and the association dictionaries define the limits of modern Russian speech in different ways, reflecting the ideas and concepts of different socio-cultural and age groups of people. The article deals with the issue of correlation between generic and specific categories in the language consciousness of people. From the logical point of view the generic categories appear as categories ofhigher level as compared to the specific ones. However, in the structure of ordinary (not scientific) language consciousness they do not necessarily occupy the same place. The totality of concepts about the style that modem Russian people possess is based on the concrete, specific phenomenon, which is the starting point of moving to the more abstract generic notion. In accordance to this idea the author i.nterprets the meaning of the word stil·.